3=60-x

Simple and best practice solution for 3=60-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=60-x equation:


Simplifying
3 = 60 + -1x

Solving
3 = 60 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
3 + x = 60 + -1x + x

Combine like terms: -1x + x = 0
3 + x = 60 + 0
3 + x = 60

Add '-3' to each side of the equation.
3 + -3 + x = 60 + -3

Combine like terms: 3 + -3 = 0
0 + x = 60 + -3
x = 60 + -3

Combine like terms: 60 + -3 = 57
x = 57

Simplifying
x = 57

See similar equations:

| -4(n+3)=-3n-2 | | 21-x=8 | | 3(4-8)=1/5(35x+30) | | -7(6+8r)-3r=17 | | 2y+x+-2x+3x=180 | | (1-x)+x=1.008 | | ln(7x-4)=lm(2x+11) | | 3x^3+7x^2+4x= | | 0.2(p+4)-0.7(p+2)=-3 | | 27x+21= | | (5x^2-30)/150x=1/6 | | a=22/7x45/2² | | 10-8(3-s)+5(s+3)=30 | | 30x^2-38x+12=0 | | 22/7(45/2)² | | X+3=(X-1)*2 | | 7y-25=-33+6y | | 20x^2-11-4= | | 4n^2-39+95=0 | | 5y-14=-22+y | | 3(q-3)+4q-1=5q+5+2q | | X^2+2ax=b | | -51=7(-1+6p)-6(7+7p) | | 3m+7+3(3m-4)-4(m+4)=0 | | 100=1/2*5t^2 | | 100=1/2(5)t^2 | | d=8sin(6) | | 8x^3+27x^2+12x-11=0 | | x^2-9y^2-4x-18y-14=0 | | 2b^2+16b+35=0 | | 3/4y=32 | | 1+1+x=15891769817369875983457193761439856813945619865198365190645 |

Equations solver categories